Community Behavior Regarding the Control of Dengue Hemorrhagic Fever in East Nusa Tenggara: Literature review - Sali, Tredesia Eda; Landudjama, Leni; Toru, Veronika (Journal of Tropical Diseases and Health Science, 2023)
Dengue Hemorrhagic Fever (DHF) is a disease caused by the dengue virus through the bite of the Aedes sp mosquito with Aedes aegypti as the main vector and Aedes albopictus as the secondary vector. The number of DHF sufferers in East Nusa Tenggara (NTT) Province increased until 2020, with 4,518 people infected and 48 people died. This research aims to determine the description of community behavior regarding disease control (DHF) in East Nusa Tenggara. Method: Using literature review research with problem identification stages, data search using Google Scholar, Science Direct, ProQuest databases with the keywords "community behavior about controlling dengue hemorrhagic fever in East Nusa Tenggara". The articles reviewed were 10 articles with publication years from 2019-2020. Based on the results of the review of 10 articles analyzed, it was found that most people have good knowledge and attitudes towards controlling Dengue Hemorrhagic Fever (DHF). However, these results are not fully followed by optimal preventive actions and behaviors. The mismatch between knowledge and actual practices indicates a behavioral gap that is still a major challenge in controlling DHF in the community. Socioeconomic factors, environmental habits, and the weak monitoring function of health cadres also exacerbate the situation. A sustainable community empowerment strategy is needed through community-based education, cadre mentoring, and cross-sector support to strengthen changes in DHF prevention behavior in a sustainable manner.